The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/biology9080203
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Ameliorates Insulin Resistance of Type 2 Diabetes through Motivating Short-Chain Fatty Acid-Mediated Skeletal Muscle Cell Autophagy

Abstract: Background: Exercise can ameliorate type II diabetes mellitus (T2DM) by regulating intestinal flora metabolites. However, the detailed mechanism needs to be further explored. Methods: A T2DM model using mice was established by feeding them a high-fat diet and giving them subsequent streptozocin injections. Fasting blood glucose and serum insulin were determined by blood glucose meter and radioimmunoassay, respectively. Intestinal flora was measured by 16sRNA sequencing. SCFA content was measured by gas chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 66 publications
(75 reference statements)
0
43
1
Order By: Relevance
“…The result present that Probioglu TM would significantly elevate mRNA level of Occludin, JAM-A and ZO-2 by comparing to medium control [41]. S1 Besides, researchers had demonstrated exercise could ameliorate T2DM induced intestinal SFCA concentration decline in mice model [42]. It is reported that probiotic secreting SCFA would improve glycemic control among T2DM patients [43].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The result present that Probioglu TM would significantly elevate mRNA level of Occludin, JAM-A and ZO-2 by comparing to medium control [41]. S1 Besides, researchers had demonstrated exercise could ameliorate T2DM induced intestinal SFCA concentration decline in mice model [42]. It is reported that probiotic secreting SCFA would improve glycemic control among T2DM patients [43].…”
Section: Discussionmentioning
confidence: 95%
“…Besides, researchers had demonstrated exercise could ameliorate T2DM induced intestinal SFCA concentration decline in mice model [ 42 ]. It is reported that probiotic secreting SCFA would improve glycemic control among T2DM patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“… 134 Besides, the binding of SCFAs to the FFAR2 receptor might ameliorate insulin resistance by promoting autophagy of skeletal muscle cells. 138 …”
Section: Beneficial Roles Of Scfa In Cardio-metabolic Health and Invomentioning
confidence: 99%
“…Knockout mice for GPR43 are obese under normal diet, whereas overexpression of the receptor leads to inhibition of fat accumulation. In a mouse model of T2DM, exercise training reversed the reduction in intestinal and plasma SCFA and improved SM IR by inducing muscle cell autophagy ( 100 ). Moreover, SCFA are key modulators of IGF-1 synthesis ( 101 ), which may provide a further link between SM metabolism and gut microbiota.…”
Section: Pathophysiology Of Dysmetabolic Sarcopeniamentioning
confidence: 99%